Perancangan Mesin Pencetak Paving Blok Hexagonal Diagonal 20 CM - Edi Rande; Jasman Jasman (Syntax Corporation Indonesia, 2023)
Paving blocks are one of the most needed materials in rural and urban areas. In the East Luwu region, most of the paving blocks are produced by manual manufacture which takes a long time. Making paving blocks manually usually only compacts the sand grains that are collected or pounded on the mold. This method allows for air voids between the grains of sand which causes a decrease in the quality of the paving blocks. The purpose of this research or final project is to design a paving block making machine in the shape of a hexagonal with a diagonal of 20 cm that uses a hydraulic power press. The design consists of designing the form of the arrangement of the drawings and parts, the design of the manufacture, maintenance and work safety. The design result is a Hexagonal Block Paving Machine with a diagonal of 20 centimeters consisting of a hydraulic system, mold components, and a vibrating machine supported by a C profile steel frame (chanel steel) with a compression force of 3.2 tons. The hexagonal block paving machine with a diagonal of 20 centimeters is designed to produce eight paving blocks at one time.